2015
DOI: 10.1371/journal.pone.0130120
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Motor Representation of Rhythm in Fronto-Parietal Cortical Areas: An fMRI Study

Abstract: When sounds occur with temporally structured patterns, we can feel a rhythm. To memorize a rhythm, perception of its temporal patterns and organization of them into a hierarchically structured sequence are necessary. On the other hand, rhythm perception can often cause unintentional body movements. Thus, we hypothesized that rhythm information can be manifested in two different ways; temporal and motor representations. The motor representation depends on effectors, such as the finger or foot, whereas the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
1
24
0
3
Order By: Relevance
“…Previous fMRI data have indicated that the HMS is implicated in the processing of action-related information, such as executing actions [22], perceiving actions [e.g., 23,28,35], and imagining actions [e.g., 22,25]. Some evidence also suggests that a mirror-like system is implicated in producing musical stimuli [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous fMRI data have indicated that the HMS is implicated in the processing of action-related information, such as executing actions [22], perceiving actions [e.g., 23,28,35], and imagining actions [e.g., 22,25]. Some evidence also suggests that a mirror-like system is implicated in producing musical stimuli [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the HMS can be recruited by musical activities such as watching piano performances [39,40], tapping to rhythms [41], and making emotional judgments of songs [42]. Furthermore, prior studies have also shown the engagement of a network of activity resembling the HMS during reproducing melodies [43] and rhythmic patterns [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Что же касается группы контро-ля, то очевидно, что для этих детей удержание более быстрых ритмов (90 и 120 уд/мин) было легким зада-нием, так как стандартное отклонение от заданного ритма и дисперсия воспроизводимых интервалов при этом оказались ниже, чем при воспроизведении рит-ма в 60 уд/мин. Известно, что мозжечок участвует не только в про-дуцировании ритмичных движений, но и в их вос-приятии (перцепции) [9,12,37]. По-видимому, дети с поражением области мозжечка вследствие опухоли ЗЧЯ хуже различают ритмы, что может объяснить одинаковую вариативность в воспроизведении рит-мов с разными частотами этими детьми.…”
Section: Fig 3 Individual Dependence Of the Error Module Of The Timunclassified
“…Восприятие и воспроизведение ритмических пат-тернов является комплексным согласованным про-цессом одновременной работы слуховых, моторных и префронтальных областей коры больших полуша-рий [7][8][9]. Слухо-моторная синхронизация предпо-лагает как тщательность слуховой обработки для бо-лее точного оценивания временных интервалов, так и строгий моторный контроль над совершаемым дви-жением, а также тонкую координацию между ними [6].…”
unclassified
See 1 more Smart Citation